(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article covers the socio-psychological analysis of the family and its similar concepts, and theoretical analysis contributed to a more thorough analysis of the family phenomenon, illuminating the views of foreign scientists.